Estudo sobre a rotatividade em um frigorífico de aves localizado na região norte do Estado do Rio Grande do Sul - Almeida, Luiza Yasmin Oliveira de (2022)
This article seeks to measure employee turnover rates in an important poultry slaughterhouse located in the northern region of the state of Rio Grande do Sul and, thus, identify its possible causes and propose reduction alternatives through an action plan. The overall objective is to assess the impact of turnover on the slaughterhouse's performance and the specific objectives are to identify the company's turnover levels, analyze the reasons for higher levels and build an action plan. This is an exploratory research using quantitative data for its analysis. Primary data were collected through interviews and secondary data through records provided by the company. Through the analysis, a high level of turnover was identified compared to the acceptable average in the market.